COMPARATIVE DYNAMIC RESPONSEANALYSIS OF OFFSHORE WIND TURBINES FENDER IN SHIP COLLISION - HAN ZhiWei; LI Chun; YU Wan; DENG YunHe; LIU JiHong (Jixie qiangdu)
With the development of offshore wind farms,the probability of collision between offshore wind turbines and ship will gradually increase. Studying the anti-collision performance of offshore wind turbines has important application background and value. Piles-soils coupling as a condition,contrast the rubber、aluminum foam crashworthy device,and explict dynamics software LS-DYNA is used to simulate the process of marine wind turbines being hit by ships. Compared with foam aluminum guards,rubber guards and unprotected wind turbines,the wind turbine is subjected to the dynamic response of the ship collision process.The results show that With the increase of the speed of the ship,the maximum contact force of the rubber material increases,while the foam aluminum material increases first and then decreases,and its energy absorption characteristics are enhanced after the 6 m/s; with the comparison of the protective device aluminum foam、rubber and non-protective device,the aluminum foam material has the best inhibition to the structure response; the more dense the plastic strain contour line,the larger the plastic deformation,and the plastic deformation is easy to occur when the oblique support is connected with the column.